The Internal and Foreign Political Situation of the First Republic of Armenia in the First Months of Independence - Petrosyan, Gegham; Petrosyan, Lusine (YSU Journal of International Affairs, 2021)
The article covers the unspeakably challenging socio-economic and political situation in the First Republic of Armenia during the first months of the country’s independence, the development of the draft program of the provisional government to get the country out of a difficult situation in 1918 in June-July. The draft program contained the main directions and priorities of the country’s domestic and foreign policy strategy.
Keywords: Republic of Armenia; Ottoman Turkey; Russia; political situation; Hovhannes Kajaznuni; interim government; domestic policy; foreign policy